Maternal hemoglobin: socio-demographic and obstetric determinants in rural Central India - Tayade, Surekha; Singh, Ritu; Kore, Jaya; Gangane, Neha; Singh, Noopur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal Anemia is a global health problem with adverse implications on materno-fetal outcome. Various socio-demographic and obstetric factors affect prevalence of anemia. Methods: A hospital based, cross-sectional, observational study was carried out among pregnant women seeking antenatal care at Kasturba Hospital of MGIMS, Sewagram, a rural tertiary care institute in central India. Information was collected about demographic variables, age, gravidity, parity, literacy, area of residence and socioeconomic status. Hemoglobin levels in first trimester and pre delivery were measured by coulter and correlated with socio-demographic and obstetric factors. Results: Among 500 pregnant women of first trimester, 249 (49.8%) had anemia, 154 (30.8%) mild, 86 (17.2%) moderate and 9 (1.8%) severe anemia. More women with anemia were of lesser age, resided in rural area, belonged to middle and lower economic class, lived with joint families and had less than 12 years of formal education. Conclusions: Anemia is prevalent in pregnant women in this geographic region of central India. Age, higher gravidity, higher parity, rural residence, low socioeconomic status and less than 12 years of formal education, are risk factors. Appropriate age at marriage, small family norm, education of girl child, anemia prevention strategy in adolescent girls and financial empowerment of women are suggested strategies for prevention of anemia and improved maternofetal outcome.